24.1k views
1 vote
Multiply (2a - 3)(3a + 4). Write your answer in standard form

User DavidRguez
by
5.4k points

2 Answers

5 votes

Answer:

6a² - a - 12

Explanation:

FOIL Method.

First (2a * 3a) = 6a²

Outer (2a * 4) = 8a

Inner (-3 * 3a) = -9a

Last (-3 * 4) = -12

6a² + 8a - 9a -12

6a² - a - 12

User Tharsan Sivakumar
by
5.1k points
0 votes

Answer:


6a^2-a-12

Explanation:

we have the expression:


(2a - 3)(3a + 4)

to solve this problem we need to multiply the elements of the first parenthesis (2a -3) by the elements of the second parenthesis (3a + 4), and we will get the following:


(2a - 3)(3a + 4)=2a*3a+2a*4-3*3a-3*4

and simplifying the resulting expression we get:


(2a - 3)(3a + 4)=6a^2+8a-9a-12

finally, putting together like terms, we get the answer in standard form:


(2a - 3)(3a + 4)=6a^2-a-12

User Grant Thomas
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.